2022
DOI: 10.3390/healthcare10122339
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Healthcare Professionals in Germany: A Questionnaire Survey Evaluating Discrimination Experiences and Equal Treatment at Two Large University Hospitals

Abstract: Objective: To identify facilitators and barriers and derive concrete measures towards better workplace integration of migrants working in the German healthcare sector. Design: Two-centre cross-sectional quantitative online survey of experiences of discrimination among healthcare professionals with a migration history in two large German university hospitals. Participants: 251 participants fully completed the questionnaires. Main outcome measures: Experiences of discrimination and perception of inequality. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…While migrant healthcare workers being subjected to overt or subtle racism, discrimination, and marginalisation is sadly reported in several other studies, it is not acceptable and indicates a need for change and enhanced diversity, equity and inclusion training for all involved. 29 Of particular concern in this research is the fact that when applicants sought help for their situation due to their lack of formal status as a student or registered pharmacist, there was no formal route available. Of note, while this research was being conducted, the PSI commenced a review of the TCQR process and identified a number of changes to be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…While migrant healthcare workers being subjected to overt or subtle racism, discrimination, and marginalisation is sadly reported in several other studies, it is not acceptable and indicates a need for change and enhanced diversity, equity and inclusion training for all involved. 29 Of particular concern in this research is the fact that when applicants sought help for their situation due to their lack of formal status as a student or registered pharmacist, there was no formal route available. Of note, while this research was being conducted, the PSI commenced a review of the TCQR process and identified a number of changes to be implemented.…”
Section: Discussionmentioning
confidence: 99%